Modeling Epilepsy Using Human Induced Pluripotent Stem Cells-Derived Neuronal Cultures Carrying Mutations in Ion Channels and the Mechanistic Target of Rapamycin Pathway - Weng, Octavia Yifang; Li, Yun; Wang, Lu-Yang (Frontiers in Molecular Neuroscience, 2022)
Epilepsy is a neurological disorder that affects over 65 million people globally. It is characterized by periods of seizure activity of the brain as a result of excitation and inhibition (E/I) imbalance, which is regarded as the core underpinning of epileptic activity. Both gain- and loss-of-function (GOF and LOF) mutations of ion channels, synaptic proteins and signalling molecules along the mechanistic target of rapamycin (mTOR) pathway have been linked to this imbalance. The pathogenesis of epilepsy often has its roots in the early stage of brain development. It remains a major challenge to extrapolate the findings from many animal models carrying these GOF or LOF mutations to the understanding of disease mechanisms in the developing human brain. Recent advent of the human pluripotent stem cells (hPSCs) technology opens up a new avenue to recapitulate patient conditions and to identify druggable molecular targets. In the following review, we discuss the progress, challenges and prospects of employing hPSCs-derived neural cultures to study epilepsy. We propose a tentative working model to conceptualize the possible impact of these GOF and LOF mutations in ion channels and mTOR signalling molecules on the morphological and functional remodelling of intrinsic excitability, synaptic transmission and circuits, ultimately E/I imbalance and behavioural phenotypes in epilepsy.